Effect of PZT particle size on dielectric and piezoelectric properties of PZT-cement composites - Chaipanich A. (2014)
In this work, the effect of PZT particle size on the properties of PZT-PC composites was investigated. PZT of various median particle sizes (3.8-620 μm) were used at 50% by volume to produce the composites. The results showed that the dielectric properties of the composites increased marginally with PZT particle size where εr = 176 and 167 for composites with 620 μm and 3.8 μm PZT particle size, respectively. A noticeable increase in d33 values was also found when the particle size was increased where the composite with 620 μm PZT particles size was found to have d33 value of 26 pC/N compared to 17 pC/N for the composite with 3.8 μm PZT particle size. The enhancement in the dielectric and piezoelectric properties was contributed to lesser contacting surfaces between the cement matrix and the PZT particles. © 2006 Elsevier B.V. All rights reserved.